Antioxidant Activity of Fruit Extract Powder Beans (Phaseolus vulgaris L.) Using DPPH Method - Rizki Nugrahani; Yayuk Andayani; Aliefman Hakim (Postgraduate, University of Mataram, 2020)
Free radical effect is one of many factors that can cause coronic desease, heart coronary desease, diabetes militus. Beans plant (Phaseolus vulgaris L.) countant antioxidant compound. Antioxidants could inhibit oxidation reaction, that is cousing free radical compounds. The objective of this research was to determine the potential of bean extracts as an antioxidant. DPPH method was used to measure antioxidant activity, absorbances was measured using UV-Vis spectroscopy. Scrining phytochemical used to identified secondary metabolites in samples. The result showed IC50 1268.18; 2512; 1698.18 and 4442.75 μg/mL for all variety of stroge (less 1, 1, 2, 3 months) and IC50 control BHT was 1.744 μg/mL. Extract of bean powder sample classified as very weak antioxidant activity, variety of storage could effect to antioxidant activity. Phytochemical screening results obtained flavonoids, phenols, alkaloids, saponins, steroids and terpenoids present in the sample, while tannin are not included in the sample